[分解6×2

发布时间:2019-02-12 浏览:
质量响应
6X-7X-5 =(2X + 1)(3×-5)12A + 14A-10 = 2(图6a + 7A-5)= 2(2A-1)(3A + 5)6(XY)+ 5(YX3 x?3y?5)3a×b(3y?3y?5)3a + b(xy)+ 1 =[2(xy)10(x + 2)-29(x + 2)+ 10(x + 2)+ 10 y(x + 1)=(5x - 8)(2x - 1)2a ^ 4- 3a - 14 = 2(a)-3a - 14 =((M + n)x +(m + n)x + m n =[(a + 2)m + n)x + m][(m?n)x + n]2(6 x + x) - 9(6 x + x)+ 5?
2(6 x + x) - 9(6 x + x) - 5?
(6 x + x)-5]=(12 x + 6 x + 1)((6 x + x) - 9(6 x + x)6×+ X-5)=(12×6×+ + 1)(6×?5)(X + 1)×?3XY + 2Y + X?2?
x - 3 xy + 2 y + x - 2 y
向业主提议:在这件事上,一下子做完,不要做。多个问题
当许多朋友看到这么多问题的问题时,他们会“闪现”。